Exploring the effect of novel non-fumigant nematicides on the biological interaction between Meloidogyne incognita and pointed gourd (Trichosanthes dioica Roxb.) for sustainable management of plant-parasitic nematode - Sujan Biswas; Shantanu Bista; Debashis Roy; Shanowly Mondal Ghosh; Suddhasuchi Das; Subhadip Kar; Gautam Chakraborty (Journal of Agriculture and Food Research)
The root-knot nematode (RKN), Meloidogyne incognita, is one of the major threats to pointed gourd (Trichosanthes dioica Roxb.) cultivation in tropical Asia. Besides consuming as a vegetable, this cucurbitaceous crop is well-known for its exceptional nutritional and medicinal properties across the globe. As chemical control using soil fumigants is restricted for RKNs, selecting novel nematicidal products is crucial for the sustainable management of M. incognita. However, owing to the known variation in the field efficacy of nematicides within plant genera and soil environments, it is unclear if trifluoro nematicides will be as effective against M. incognita in pointed gourd as in solanaceous crops. Using several laboratory and field experiments, this study examined the in vitro susceptibility of M. incognita to six non-fumigant nematicides and their field effectiveness in suppressing M. incognita infestation on pointed gourd in two different soil types. Fluopyram exhibited higher toxicity against both egg (LC50 value 2.36 mg L−1) and J2 (LC50 value 1.49 mg L−1) stages of M. incognita with the significantly lowest percent of egg hatching rate at ≥ 0.5 and ≥0.1 mg L−1 on 3- and 6-days post-incubation, respectively, relative to that of other tested nematicides. Although the J2 motility rate was significantly lower in all the tested concentrations of fluopyram, fluazaindolizine, and fluensulfone after 72 h incubation, the latter reduced the root infectivity to a greater extent. The fluorinated nematicides significantly reduced the M. incognita population in soil with a lower root gall index, reproduction factor, and egg mass in the pointed gourd roots under field conditions, however, the overall efficacy of fluensulfone was higher in sandy loam than clay loam soil. Plant vigor, yield, and biochemical components of pointed gourd plants were also enhanced in fluopyram treatment compared with carbofuran. The data is crucial for site-specific RKN management in pointed gourd.